KEEFEKTIFAN INTERACTIVE E-BOOK IPA UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA SMP PADA MASA PANDEMI COVID-19 - Hana Puspitasari; Insih Wilujeng; Djuniar Rahmatunisa Haristy (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study aims to describe interactive e-book effectiveness of improving students's scientific literacy skills during the Covid-19 pandemic. This research type is quantitative descriptive with one group pretest-posttest design. The research subjects were 23 students of class VIII SMP Piri 1 Yogyakarta. The results showed that after using IPA Interactive e-book, scientific literacy skills could increase significantly. The increase in students' scientific literacy skills in competency dimensions increased by 40% and it has increased by 30% in the knowledge dimension. It can be concluded that interactive science e-book is effective for improving students' scientific literacy skills. Keywords: interactive e-book, scientific literacy, covid-19